Exploring the impact of physical exercise on mental health among female college students: the chain mediating role of coping styles and psychological resilience - Cao, Longan; Ao, Xiaorong; Zheng, Zhirong; Ran, Zhengban; Lang, Jun (Frontiers in Psychology, 2024)
Background Female college students are a high-risk group for psychological conflicts, and they are more likely to adopt negative coping styles under stress, which can lead to anxiety, depression, and other psychological problems, as well as pose hidden threats to the healthy development of school education and social work. Although physical exercise is an important means of effectively alleviating the psychological health of female college students, and there may be a close relationship between coping styles and psychological resilience with physical exercise and psychological health, specific ways to promote the psychological health of female college students by influencing their coping styles and enhancing their psychological resilience have yet to be explored. Methods The present study employed a cross-sectional design to investigate a sample of Chinese undergraduate female college students. A total of 659 participants were recruited during the second half of the 2023–2024 academic year, and they all completed assessments including the Physical Activity Rating Scale, College Mental Health Scale, Brief Coping Styles Questionnaire, and Psychological Resilience Scale. Subsequently, descriptive statistics were utilized to analyze the obtained reliable data. Results and conclusion The study revealed two significant correlations among female college students, namely the associations between physical exercise, coping styles, psychological flexibility, and mental health. Specifically, physical exercise exhibited a positive relationship with positive coping styles and psychological resilience while displaying a negative association with negative coping styles and mental health. Moreover, psychological resilience demonstrated a positive correlation with positive coping styles but displayed negative relationships with both negative coping styles and mental health. Additionally, there was a negative relationship observed between positive coping styles and mental health. Furthermore, it was found that physical exercise significantly impacted the mental health of female college students in a detrimental manner; meanwhile, coping styles and psychological resilience played crucial mediating roles in linking physical exercise to mental health outcomes. Ultimately, our mediation model sheds the underlying mechanisms through which physical exercise predicts mental health levels among female college students; these findings underscore the importance of promoting physical exercise as an effective means to enhance overall well-being.